2007
DOI: 10.1002/jbm.a.31185
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast response to fluid induced shear depends on substrate microarchitecture and varies with time

Abstract: Osteoblasts are exposed to fluid shear in vivo but the effects are not well understood, particularly how substrate properties or length of exposure modify the response. Short exposure (1 h) to shear reduces the stimulatory effect of micron-scale surface structure on osteoblast differentiation, but the effects of longer term exposures are not known. To test the hypothesis that substrate-dependent responses of osteoblasts to shear depend on the length of exposure to fluid flow, MG63 osteoblasts were grown on tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
(66 reference statements)
4
15
0
Order By: Relevance
“…COX-2 is vital for the production of PGE 2 25 and the increase in COX-2 expression resulted in higher PGE 2 production in all flow groups over the static control at both 25 and 49 h. PGE 2 is involved in osteoblast differentiation 26 and may be linked to osteocalcin expression. 27,28 In 2D studies, it has been found that PGE 2 release is similar for continuous and short-term rest-inserted loading, a finding which is similar in 3D in this case. 19 COL-1 expression decreased for all bioreactor groups compared with the static control.…”
Section: Discussionsupporting
confidence: 68%
“…COX-2 is vital for the production of PGE 2 25 and the increase in COX-2 expression resulted in higher PGE 2 production in all flow groups over the static control at both 25 and 49 h. PGE 2 is involved in osteoblast differentiation 26 and may be linked to osteocalcin expression. 27,28 In 2D studies, it has been found that PGE 2 release is similar for continuous and short-term rest-inserted loading, a finding which is similar in 3D in this case. 19 COL-1 expression decreased for all bioreactor groups compared with the static control.…”
Section: Discussionsupporting
confidence: 68%
“…48 Studies in healthy volunteers have shown that selective COX-2 inhibitors reduce prostacyclin (PGI 2 ) formation. 37,38 Taken into account with other studies, 49,50 these data indicate that 60%-70% of PGI 2 production in healthy humans is derived from COX-2. Thus, COX-2 would be the predominant COX isoform in the vascular endothelium, and would be directly associated with prostacyclin production in normal circulation.…”
Section: Biological Basis For Cardiovascular Complicationssupporting
confidence: 66%
“…Adapted from Grosser et al 50 (CI 50 COX-1/CI 50 COX-2; the higher the value, the higher the COX-2 selectivity). CI 50 : necessary concentration of the drug to inhibit 50% of COX-1 or 50% of COX-2.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…55 Additional work has suggested osteoblast and osteocyte behavioral response to fluid flow is further modulated by the surface micro-architecture of the cell substrate. 56 Generally, in both in vitro and in vivo studies, bone cells have shown sensitivity to dynamic fluid shear, which has led directly to its exploration as a mechanical stimulation modality in ASC, as discussed in section Fluid flow and shear stress. 34 Uniaxial tensile strain has been used as another mode of mechanical stimulation to successfully induce bone regeneration in vivo via distraction osteogenesis.…”
Section: Figmentioning
confidence: 99%